Burnout and its relationship with personality risks in a sample of doctors from south Ecuador - Marina R. Ramírez; Mercy P. Ontaneda; David Ortega Jiménez (INFAD, 2019)
Burnout is a global phenomenon, especially in the field of health professionals because of the characteristics of these professionals would be more vulnerable (Gluschkoff, Elovainio, Kinnunen, Mullola, Hintsanen, Keltikangas-Järvinen and Hintsa, 2016). The objective of this research was to identify burnout and the relationship with personality traits (extroversion, psychoticism, neuroticism). A descriptive and correlational methodology was used, with a non-probalistic accessibility sample of 149 physicians from the southern area of Ecuador. The instruments used were the Maslach Inventory [MBI-HSS] and the Eysenck Revised Personality Questionnaire- [EPQRA]. Among the relevant results, a 2.7% prevalence of burnout syndrome was obtained, in terms of emotional exhaustion 25.5% a high level, in depersonalization 10.7% a high level and 59.1% have low personal achievement. As general conclusions we could identify a significant correlation between neuroticism and burnout and emotional exhaustion dimensions; depersonalization, as well as between extroversion and depersonalization.